Three decades of misrecognition: defining people with disability in Australian higher education policy - Pitman, Tim; Brett, M.; Ellis, Katie (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
In Australia, the Disability Discrimination Act and associated Educational Standards prevent educational institutions from treating people with disability less favourably than those without disability–directly or indirectly. However, people with disability are still subject to both economic and cultural disadvantage in Australian higher education policy. In this article we describe this as a ‘recognition–redistribution dilemma’, whereby this population must both deny and claim their subjectivity. This is in large part due to the lack of transparency around how disability is defined, coded and recorded. Drawing on three stages of development of Australian higher education equity policy across three decades of higher education disability policy, the article provides insights into how people with disability have been categorised, classified and counted in higher education and the implications this has for how they are supported.Points of interest Australian higher education institutions ask students with disability to identify not only that they have disability, but the ‘category’ of disability and whether or not they need support. The disability categories used are not fit for purpose and it is not clear whether the data being collected have value, in terms of how they advance social understandings of disability. Disability support staff understand and advocate for the need to focus on functional support, not disability definitions, but the policy and reporting environment does not reflect this need. Higher education institutions should only collect information from people with disability if it is needed to support the person specifically, or if it can be used to improve support more widely for people with disability.